Review of the Monobazus-group leafhopper genera (Hemiptera: Cicadellidae: Deltocephalinae) from the Indian subcontinent with description of five new genera and twenty-eight new species - Viraktamath, C.a.; Webb, M.d.; Yeshwanth, H.m. (Zootaxa, 2025)
A group of Asian Deltocephalinae leafhopper genera share one or more of the following features: head markings usually complex with a white diamond shaped marking apically, forewing with veins from outer apical cell (R1 and R2+3) not or variably strongly reflexed, subgenital plates moderately to greatly elongated to digitate apex, male pygofer with a dorsal or ventral process and aedeagus with one or two basal, lateral or ventral processes. This group, named here as the Monobazus group of genera, is treated in the present paper. The following genera are included: Banus Distant, Monobazus Distant, Osbornellus Ball, Mavromoustaca Dlabola, stat. nov., Phlogotettix Ribaut, Phlogothamnus Ishihara, Wanritettix Vilbaste and five new genera from the Indian subcontinent described in this paper. The new taxa recognized are: Banus curvatus sp. nov. (India: Karnataka, Kerala, Maharashtra, West Bengal), B. spiculatus sp. nov. (India: Karnataka, Kerala, Maharashtra, Tamil Nadu), Chandibanus gen. nov. with its type species Chandibanus dorsospinosus sp. nov. (India: Chandigarh), Cicurbanus gen. nov. (type species. Thamnotettix greeni Melichar), C. serratus sp. nov. (India: Karnataka, Kerala, Tamil Nadu), Lankabanus gen. nov. with its type species, Lankabanus attenuatus sp. nov., L. bispinosus sp. nov. (both from Sri Lanka), Madhyabus gen. nov. with its type species, M. reticulatus sp. nov. (India: Madhya Pradesh, Tamil Nadu), M. biligiris sp. nov. (India: Karnataka), Mavromoustaca brevispina sp. nov. (India: Punjab), M. channabasavanna sp. nov. (India: Karnataka), M. opressa sp. nov. (India: Himachal Pradesh, Mizoram, Uttarakhand), Monobazus angulatus sp. nov. (India: Karnataka, Uttarakhand), M. bannericus sp. nov. (India: Karnataka), M. biligiriensis sp. nov. (India: Karnataka, Tamil Nadu), M. bilineatus sp. nov. (India: Karnataka, Tamil Nadu), M. deccanensis sp. nov. (India: Andhra Pradesh, Karnataka, Kerala), M. longulus sp. nov. (India: Himachal Pradesh), M. nilgalaensis sp. nov. (Sri Lanka), M. paulus sp. nov. (India: Karnataka, Delhi), M. rotundus sp. nov. (Nepal), M. rubrostriatus sp. nov. (India: Karnataka, Kerala), M. sahyadricus sp. nov. (India: Karnataka, Kerala), M. shrunga sp. nov. (Nepal), M. sikkimensis sp. nov. (India: Sikkim), M. sudindicus sp. nov. (India: Tamil Nadu), Panghoella gen. nov. (type species, Banus maculosus Distant), P. nera sp. nov. (India: Himachal Pradesh, West Bengal. Myanmar. Nepal), P. sinuata sp. nov. (India: West Bengal) and Phlogothamnus umiamensis sp. nov. (India: Meghalaya). Osbornellus (Mavromoustaca) Dlabola is raised to genus level, Mavromoustaca Dlabola stat. nov. The following new combinations are proposed: Cicurbanus greeni (Melichar) comb. nov., C. cicur (Melichar) comb. nov. (both from Thamnotettix), C. notatus (Distant) comb. nov. (from Scaphoideus), Mavromoustaca arboropictus (Dlabola) comb. nov. (from Osbornellus), M. brunnescens (Pruthi) comb. nov. (from Thamnotettix), M. deviaticus (Dlabola) comb. nov. (from Osbornellus), M. macchiae (Lindberg) comb. nov. (from Circulifer), Monobazus aurantius (Xing & Li) comb. nov (from Osbornellus)., M. confuscus (Pruthi) comb. nov. (from Paralimnus), M. fanjingshanensis (Li) comb. nov. (from Phlogotettix), M. fuscovarius (Distant) comb. nov. (from Deltocephalus), M. fletcheri (Distant) comb. nov. (from Scaphoideus), M. circinatus (Yao, Zhang & Xing) comb. nov., M. acutaedeagus (Li) comb. nov., M. polymaculatus (Li & Song) comb. nov., M. productus (Li & Xing) comb. nov. and M. rugosus (Li) comb. nov. (all from Phlogothamnus), Panghoella conoidea (Xing & Li) comb. nov. (from Osbornellus), P. maculosa (Distant) comb. nov. (from Banus), P. suiyangensis (Xing & Li) comb. nov. (from Osbornellus), Phlogothamnus grimeus (Li & Wang) comb. nov. (from Phlogotettix). The following new synonyms are recognized: Thamnotettix cicur Melichar 1903 syn. nov. of T. greeni Melichar1903; Deltocephalus fuscovarius Distant 1918 syn. nov. of Monobazus dissimilis (Distant 1908). In addition, the Chinese genus Longicornus Li & Song is recorded from the Indian subcontinent for the first time (see Appendix) and its uncertain relationship to the Monobazus group is noted; two species from the Indian subcontinent are included: L. grandis (Pruthi) comb. nov. (from Monobazus) and L. longus Xing & Li. One species from China (Hainan Is.) is transferred to Monobazus, i.e., M. datianensis Xing, Dai & Li, 2008 (Scaphoidella) comb. nov. All taxa from the Indian subcontinent are diagnosed and/or described and illustrated and keys to genera and species are provided.